S,N-Heteropentacenes – Syntheses of Electron-Rich Anellated Pentacycles - Berens, Henning R. V.; Müller, Thomas J. J. (Organic Materials, 2021)
This review summarizes syntheses of S,N-heteropentacenes, i.e. electron-rich sulfur and nitrogen-embedding pentacycles, and briefly highlights selected applications in molecular electronics. Depending on the anellation mode and the number of incorporated heteroatoms, electron density can be raised by increasing nitrogen incorporation and polarizability is manifested by the sulfur content. In comparison to triacene analogues, the conjugation pathways of S,N-heteropentacenes are increased and the favorable acene-typical crystallization behavior allows for diverse application in organic electronics. Furthermore, substitution patterns allow fine-tuning the electronic properties, extending the π-systems, and supplying structural elements for further application.1 Introduction2 Thiophene-Centered S,N-Heteropentacenes2.1 Dipyrrolo-Fused Thiophenes2.2 Diindolo-Fused Thiophenes3 Pyrrole-Centered S,N-Heteropentacenes3.1 Dithieno-Fused Pyrroles3.2 Bis[1]benzothieno-Fused Pyrrole4 Fused 1,4-Thiazines4.1 Dinaphtho-Fused 1,4-Thiazines4.2 Bis[1]benzothieno-Fused 1,4-Thiazines5 Conclusions and Outlook
Keywords: heteroacenes; cross-coupling; condensations; cyclizations; modular syntheses; optoelectronics; energy conversion; materials